PROSTHODONTIC REHABILITATION OF NON SYNDROMIC TOOTH AGENESIS - Bilal Ahmed (Journal of University Medical & Dental College, 2013)
ABSTRACT Congenital Tooth Agenesis or Hypodontia is one of the most common developmental anomaly of the human dentition, presents itself with one or more missing teeth. It is a polygenetic disorder that can occur either in isolation or as a co-finding in many syndromes. The Clinical features, diagnostic characteristics and management strategies all depend on the severity of the condition, presence or absence of associated syndromes and available resources. However, a multidisciplinary team approach and early young age assessment can be the key to success in these complicated scenarios. This report states the esthetic and functional rehabilitation of a non syndromic hypodontia patient utilizing a conventional fixed partial denture prosthesis. Keywords